La Ferrassie 8 Neandertal child reloaded: New remains and re-assessment of the original collection. Issue 82 (May 2015) - Gómez-Olivencia, Asier; Crevecoeur, Isabelle; Balzeau, Antoine
Abstract: The first evidence of the partial infant Neandertal skeleton La Ferrassie 8 (LF8) was discovered in 1970, although most of the remains were found in 1973 as part of the 1968–1973 work at the site by H. Delporte. This individual and the other Neandertal children from La Ferrassie were published in the early 1980s by J.-L. Heim, and since then LF8 has been regarded as coming from a poorly documented excavation. The recent rediscovery of the box that contained the hominin bones given by Delporte to Heim in the Muséum national d'Histoire naturelle (MNHN) collection provided new fossils and helped to locate LF8 in the site: level M2 in square 1. Two visits to the Musée d'Archéologie nationale et Domaine national de Saint-Germain-en-Laye (MAN) yielded additional fossil remains from both the 1970 and 1973 excavations and resulted in the discovery of all of the notes from the excavation of H. Delporte between 1968 and 1973. Here the new fossil remains (47 after performing all possible refits), representing significant portions of the cranium, mandible, and vertebral column together with fragmentary hand and costal remains, are described. Unsurprisingly, the morphology of the bony labyrinth and of a complete stapes from the nearly complete left temporal show clear Neandertal affinities. Additionally, a complete reassessment of the original LF8 collection has resulted in the identification of several errors in the anatomical determination. Despite the significant increase in the anatomical representation of LF8, the skeletal remains are still limited to the head, thorax, pelvis, and four hand phalanges, with some very fragile elements relatively well preserved. Different hypotheses are proposed to explain this anatomical representation, which can be tested during future fieldwork. Résumé: Les premiers éléments du squelette partiel d'enfant nommé La Ferrassie 8 ont été mis au jour en 1970, puis de nombreux autres éléments ont été découverts en 1973, le tout dans le cadre de l'intervention dirigée par Henri Delporte entre 1968 et 1973 sur le site de La Ferrassie. Cet individu, ainsi que les autres enfants néandertaliens provenant du gisement, ont été publiés au début des années 80 par Jean-Louis Heim. Depuis, cette découverte est considérée comme peu documentée. La redécouverte et la réétude récentes de la boite qui contenait les restes humains, qui avait été donnée par Delporte à Heim, dans les collections du Muséum national d'Histoire naturelle, ont permis d'identifier de nouveaux restes humains et de resituer le spécimen au sein du site : carré 1 et niveau M2. Des visites au Musée d'Archéologie nationale et Domaine national de Saint-Germain-en-Laye ont livré des fossiles supplémentaires, issus des fouilles de 1970 et 1973, et ont résulté en l'identification de toutes les archives des fouilles de H. Delporte entre 1968 et 1973. Nous décrivons ici 47 nouveaux fossiles humains, après recollement de tous les éléments qui pouvaient l'être, représentant le crâne, la mandibule, la colonne vertébrale, des éléments costaux et des mains. Sans surprise, la morphologie de la cochlée et des canaux semi-circulaires, et celle d'un étrier complet provenant de l'os temporal gauche presque complet montrent des affinités néandertaliennes claires. Par ailleurs, une nouvelle analyze de la collection originelle a permis de corriger plusieurs erreurs dans les déterminations anatomiques initiales. Bien que ces découvertes accroissent considérablement la représentation anatomique de LF8, cette dernière demeure limitée à la tête, au thorax et à 4 phalanges de la main, incluant des éléments très fragiles et bien préservés. Plusieurs hypothèses pourront être testées lors de futurs travaux de terrain pour tenter d'expliquer cet état de préservation anatomique.